2007
DOI: 10.1002/psc.840
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted RCM for the synthesis of carbocyclic peptides

Abstract: Microwave irradiation dramatically improves the efficiency of ring closing metathesis (RCM) reactions of resin-attached peptides and the technology is illustrated by the highly selective synthesis of dicarba analogues of alpha-conotoxin IMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 20 publications
0
48
0
1
Order By: Relevance
“…Whether conformational exchange serves any important biological function, for example in allowing the toxin to undergo required conformational rearrangements as it engages its cognate binding site, or whether it is simply an adventitious consequence of the presence of multiple disulfide bridges in certain environments, remains to be established. One way of addressing this question is to replace some of the disulfide bridges with less flexible homologues, and means to achieve this are now available {Robinson, 2007 #99}. In parallel with such efforts, greater access to backbone relaxation data afforded by high-field spectrometers equipped with more sensitive probes should contribute to a better understanding of the relationships among structure, flexibility and activity.…”
Section: Discussionmentioning
confidence: 99%
“…Whether conformational exchange serves any important biological function, for example in allowing the toxin to undergo required conformational rearrangements as it engages its cognate binding site, or whether it is simply an adventitious consequence of the presence of multiple disulfide bridges in certain environments, remains to be established. One way of addressing this question is to replace some of the disulfide bridges with less flexible homologues, and means to achieve this are now available {Robinson, 2007 #99}. In parallel with such efforts, greater access to backbone relaxation data afforded by high-field spectrometers equipped with more sensitive probes should contribute to a better understanding of the relationships among structure, flexibility and activity.…”
Section: Discussionmentioning
confidence: 99%
“…With the discovery of air-stable catalysts that are compatible with different functional groups, RCM has emerged as a powerful tool for preparing cyclic peptides. This has been applied on several biologically active peptides, such as oxytocin [44,45], enkephalin [46,47], Bowman-Birk inhibitor [48], a-conotoxin [49] and the antibiotic peptides lacticin 3147-A2 [50] and nisin [51,52].…”
Section: Cyclization By Alkene Metathesismentioning
confidence: 99%
“…However, HPLC analysis of an aliquot of resin-cleaved, deprotected peptides (TFA/TIS/H 2 O 35 95:2.5:2.5) revealed that only 56% of the linear peptide had been cyclised. We repeated the reaction under microwave irradiation 14 for 1 h at 100ºC and, surprisingly, the efficiency of the RCM was dramatically improved (cyclic/linear peptide 93:7, 2:1 mixture of cis and trans diastereomers, respectively) 40 and no oligomerization products were detected, even using a relatively high resin loading (0.34 mmol/g). The configuration of the double bond was unambiguously established by NMR spectroscopy since a relatively strong NOE between both olefinic protons was only found in the major isomer.…”
mentioning
confidence: 99%